Economic Evaluation of Small-scale Renewable Electricity Generation Project with Community Participation by Regional I-O Analysis in which WTW is incorporated - Eiji Ohno; Ryuta Mori; Akira Matsumoto (European Regional Science Association (ERSA), 2015)
Small-scale renewable electricity generation projects have the potential to address not just the need to reduce greenhouse gas emissions to combat climate change, but also to provide local, sustainable economic and community revitalization. Japanfs experience following the Great East Japan Earthquake has also demonstrated the potential fragility of too-heavy reliance on large-scale power plants. Small-scale projects, such as those using solar, wind, or hydroelectric resources, can thus also boost a regionfs energy self-sufficiency and ability to withstand natural disasters. In addition, small-scale operations mean that areas unsuitable to larger plants or installations can become productive - in the case of hydroelectric plants, as discussed in this paper, smaller streams can be tapped for power, with the additional benefit of not requiring costly dam construction. These benefits indicate the great potential for small-scale electricity generation projects, and this paper explores their economic feasibility in practice, using a hypothetical case study in a small regional Japanese city. The hypothetical plant is intended to provide both environmental and economic benefits to the local community, and the various trade-offs between levels of each are studied. We evaluate the project economically by using the regional I-O (input output) analysis in which the WTW (willingness to work) is incorporated. The WTW results for the project have been estimated by using the conjoint analysis as a function of its various attributes, namely revenue from the projectfs electricity sales, profits earned for the local community, and rewards given to contributors. The results show that if the reward for volunteer activity is set higher, the amount of volunteer labor is increased, and the operating surplus of the project is also increased. As a result, it is possible to reduce the subsidies of regional governments with respect to the project, and it is possible to devote that amount of budget to improvement of other administrative services. Subsequently, when this type of small hydroelectric generation project with citizen participation is introduced, household utility levels increase. Understanding the dynamism between these factors can allow regional governments to adapt the scheme to best fit the needs of individual regions.
Keywords: Q42; Q51; R13; 330; small-scale renewable electricity generation; community participation; community revitalization; regional input output analysis; willingness to work